Territorialité, langue, toponymie et traité chez les Pekuakamiulnuatsh - Tipi, Sükran; Boivin, Hélène (Anthropologica, 2020)
<span style="color: #000000; font-family: 'Open Sans', Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The members of the Pekuakamiulnuatsh First Nation (Innu of Lac Saint-Jean) have been engaged in a process of territorial negotiation for more than forty years. They are now working with their partners from Regroupement Petapan to finalize a draft treaty with the federal and provincial levels of government as part of the Comprehensive Land Claims Policy. The notion of territory, which remains foundational to the identity claims of the Pekuakamiulnuatsh, remains inseparable from the relationship between language and land and from the contemporary mode of expression of this relationship in their language, <em style="box-sizing: border-box; color: #000000; font-family: 'Open Sans', Arial, sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Nehlueun<span style="color: #000000; font-family: 'Open Sans', Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">, notably through the use of toponyms, but also in the provisions set out in the draft treaty that opens the way for the self-government of future generations. The Peshunakun multidisciplinary research project, initiated by the Mashteuiatsh First Nation in 2008 in response to the need for cultural and political affirmation, highlights the very anchoring of Ilnu identity and language in space via the documentation of the history of the occupation and use of ancestral land. As such, this project sheds new light on the territoriality of this First Nation from the perspective of the relationship between its language, visions, and current political concerns.